Implementasi Media Pembelajaran Berbasis Web Google Sites Untuk Meningkatkan Kemampuan Memecahkan Masalah Siswa SMA Pokok Bahasan Gelombang Bunyi - Maryani Maryani; Bambang Supriadi; Meidia Sariyatun Nisak (Postgraduate, University of Mataram, 2022)
The use of instructional media is very necessary in learning physics, because many abstract phenomena and natural phenomena are difficult to understand both by students without the right means. Sound wave material which is dominated by theories and concepts requires a learning media that packs concepts to be effective and improves students' problem solving abilities. Problem solving ability is one of the goals of forming 21st century skills. The times have also brought progress in education, including interactive multimedia-based learning media such as web-based learning media such as Google sites. This study aims to determine the application of learning media based on google sites web-based learning media, the subject of sound waves to improve students' ability to solve physics problems. The type of research used is descriptive quantitative with the research design of MDLC (Multimedia Development Life Cycle). The research subjects were 31 students at XI MIPA 1 MAN 1 Situbondo. Web-based learning media google sites is declared effective in improving students' problem-solving skills if they meet the criteria for the average level of effectiveness of the n-gain score. The n-gain data was obtained through the students' pretest and posttest scores, and the average pre-test score was 59.35 and the post-test average score was 76.74. While the average percentage of N-gain is 44.03% which states the medium category, meaning that the developed web learning media can improve the problem solving ability of physics students. The student response questionnaire after using the media is in the very good category, with the average percentage of student responses to the learning media that has been given which is 82%. The results of these data indicate that the learning media has an attractive design for students and easy operation. So it can be concluded that the google sites web-based learning media with the subject of sound waves meets the criteria of a good learning media and is able to improve students' problem solving skills at MAN 1 Situbondo